2016
DOI: 10.1002/pc.24111
|View full text |Cite
|
Sign up to set email alerts
|

Improved mechanical properties of positive‐pressure filtered CNT buckypaper reinforced epoxy composites via modified preparation process

Abstract: In the present study, a positive-pressure filtration method was proposed to prepare carbon nanotube buckypapers (CNT BPs) with desirable porosity and mechanical properties. The obtained BPs were then infiltrated with epoxy via vacuum-aided resin transfer molding (VARTM) process without the use of a solvent. Some of the impregnated composites were directly cured under a vacuum pressure. The others were put into a hot-press to cure under a higher pressure of 0.7 MPa. Results have shown that the tensile strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…And then it was immersed into nitric acid for 1 min to remove residual surfactant, subsequently washed with distilled water to remove impurities and acid, finally dried at 60°C for 24 h in an oven, thus porous and free-standing CNT BP was obtained (shown in Figure 1b), details can be referred to our previous study. 50 The average thickness and diameter of the obtained CNT BP are respectively measured as about 0.03 mm and 280 mm. As can be seen from Figure 1b that the CNT BP is porous, when it is introduced into the interfaces of the CFRP laminates, the epoxy matrix would flow into the porosities during the cure process and then form integrated interfaces.…”
Section: Methodsmentioning
confidence: 95%
“…And then it was immersed into nitric acid for 1 min to remove residual surfactant, subsequently washed with distilled water to remove impurities and acid, finally dried at 60°C for 24 h in an oven, thus porous and free-standing CNT BP was obtained (shown in Figure 1b), details can be referred to our previous study. 50 The average thickness and diameter of the obtained CNT BP are respectively measured as about 0.03 mm and 280 mm. As can be seen from Figure 1b that the CNT BP is porous, when it is introduced into the interfaces of the CFRP laminates, the epoxy matrix would flow into the porosities during the cure process and then form integrated interfaces.…”
Section: Methodsmentioning
confidence: 95%
“…5 The mechanical properties can be improved by in situ doping carbon nanotubes (CNTs) in the resin-rich zone between plies because CNTs have a high specific surface area, high specific stiffness, high specific strength, and unique chemical properties, which are considered as ideal reinforcing phase for polymer composites. 6,7 For example, Zhang et al 8 dispersed CNTs on the surface of CF/PEEK prepreg by solution volatilization method. The CNTs/CF/ PEEK multiscale composites were prepared by AFP and the interlaminar shear strength was improved.…”
Section: Introductionmentioning
confidence: 99%
“…There are two general routes to prepare BPs: chemical vapor deposition (CVD) and filtration (vacuum and positive pressure methods). [ 16–21 ] Previous works have demonstrated that mechanical performances of BPs obtained by CVD are higher than that prepared by filtration, because of the linking effect of catalyst nanoparticles among CNTs. However, this also creates an issue that it is difficult to completely remove the catalyst impurities resulted from the CVD process, thereby limiting their further applications.…”
Section: Introductionmentioning
confidence: 99%